Higher one-year achievement rate of serum phosphate associated with lower cardiovascular mortality in hemodialysis patients - Weichen Zhang (BMC, 2021)
Abstract Background Estimation of phosphate load in hemodialysis patients is always controversial in clinical practice. The aim of this study was to verify individual achievement rate of serum phosphate as the evaluation of phosphate load through investigating its impact on cardiovascular mortality in hemodialysis patients. Methods This was a single-center, retrospective cohort study. A total of 251 maintenance hemodialysis patients were enrolled. The individual achievement rate of serum phosphate was defined as the times of tests within the target range divided by total times of tests over a period of time. Cox regression model was used to examine the relationship between individual achievement rate of serum phosphate and cardiovascular mortality. Results The mean age of the study population was 61 ± 13 years old. A total of 44 (17.5%) patients died from cardiovascular disease (CVD) during a median follow-up of 65 months. Multivariable Cox analysis showed that one-year serum phosphate achievement rate of 0% (HR = 4.117, P = 0.016) and 25% (HR = 3.343, P = 0.023) increased the risk of cardiovascular mortality while the achievement rate of 50% (HR = 2.129, P = 0.162) and 75% (HR = 1.080, P = 0.902) did not, compared to the rate of 100%. Urea reduction ratio (URR) was positively, while serum intact parathyroid hormone (iPTH), alkaline phosphatase (ALP), normalized protein catabolic rate (nPCR), and total phosphate-binding capacity of drug were negatively associated with achievement in target of serum phosphate. Conclusions Keeping one-year achievement rate of serum phosphate higher than 50% provides significant clinical benefits in reducing cardiovascular mortality.